Advances in Solid State Physics 45 - Kramer, Bernhard (Advances in Solid State Physics, 2006)
The present volume 45 of Advances in Solid-State Physics contains the written versions of selected invited lectures from the spring meeting of the Arbeitskreis Festkörperphysik of the Deutsche Physikalische Gesellschaft in the World Year of Physics 2005, the Einstein Year, which was held from 4 - 11 March 2005 in Berlin, Germany. Many topical talks given at the numerous symposia are included. Most of these were organized collaboratively by several of the divisions of the Arbeitskreis. The book presents, to some extent, the status of the field of solid-state physics in 2005 not only in Germany but also internationally. It is ''nanoscience'', namely the physics of quantum dots and wires, electrical transport, optical properties, spin transport in nanostructures, and magnetism on the nanoscale, that is of central interest to the physics community. Also, soft matter and biological systems are covered. .